MOSAIC: Teaching Cultural Competence - Douglas P. Smith; Sonja Ezell; Jason Brooks (The Advocate, 2015)
Emporia State University sponsors a weekend, off-site program, MOSAIC, where participants explore issues of identity development, privilege, social inequality, and discrimination - the tenants of cultural competency. MOSAIC helps participants enhance their worldview and a greater appreciation of cultural competence through a series of large and small group activities. By creating these experiences and opportunities, participants are more apt to work effectively in a variety of situations, with a mix of culturally diverse people such as those found on a college campus. By leveraging these skills the university community can be benefited to have better outcomes.